2023
DOI: 10.1140/epjc/s10052-023-11557-0
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of the glueball resonance gas

Abstract: We study the thermodynamic properties – pressure, entropy and trace anomaly – of a gas of glueballs that includes the glueball states obtained by various lattice simulations. We show that this model, called glueball resonance gas (GRG) approach, describes well the thermal properties of the Yang–Mills sector of QCD below the critical temperature $$T_c$$ T c , provided that $$T_c$$ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…As shown in [35], when N c is large, gluons dominate: a first-order phase transition between the deconfined and confined phases at T dec ≃ 300 ∝ N 0 c MeV (see [79] for a compilation of results) is expected for any value of the chemical potential. This is utterly different from the QCD phase diagram for N c = 3 [3], which is cross-over along the T direction and first order along the µ one.…”
Section: Brief Description Of Qcd At Nonzero Temperature and Densitie...mentioning
confidence: 88%
See 2 more Smart Citations
“…As shown in [35], when N c is large, gluons dominate: a first-order phase transition between the deconfined and confined phases at T dec ≃ 300 ∝ N 0 c MeV (see [79] for a compilation of results) is expected for any value of the chemical potential. This is utterly different from the QCD phase diagram for N c = 3 [3], which is cross-over along the T direction and first order along the µ one.…”
Section: Brief Description Of Qcd At Nonzero Temperature and Densitie...mentioning
confidence: 88%
“…[44,78] (for a recent compilation and comparison of lattice results, see Ref. [79]). The glueball wave function must be colorless.…”
Section: Glueballsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, these corrections can not be all independent from each other, since they are indirectly related to the θ-dependence of the free energy in the confined phase. This can be easily understood by using hadron resonance gas models like, e.g., those discussed in [103,104], where it was shown that a determination of the glueball masses is sufficient to obtain quantitatively accurate estimates of thermodynamical quantities. Finally, it would be very interesting to study models in which s 2 and m 2 or, more generally, the θ-dependence of the spectrum, can be investigated analytically (and is non-trivial).…”
Section: Jhep05(2024)163mentioning
confidence: 99%